Prince Naris’ Designs: Memories of Birth in Monuments of Death - Swaengphol, Atipat; Chitrabongs, Chittawadi (NAJUA: History of Architecture and Thai Architecture, 2024)
His Royal Highness Prince Narisaranuvattiwongse’s design works for funeral ceremonies are a unique blend of artistic typologies, ranging from royal crematoria to Buddhist monks’ talipot fans. These are what can be aptly termed as “monuments of death.” Prince Naris infused these monuments with a personal touch, drawing from Thai beliefs associated with the day of the deceased’s birth. He devised a system of signs that encapsulate these memories of birth. This body of work has not only left a lasting impression but has also served as a guiding light for contemporary architects and artists involved in the design of royal crematoria. This article delves into the intricate ‘memory system’ of Prince Naris’ works and its continued influence since his passing. It approaches the study of these ‘monuments of death’ from three distinct theoretical frameworks: the collective memories of contemporary societies, the role of memory in linguistics, and the influence of memory on contemporary cultures. By employing these diverse theories of memory, the article aims to provide a comprehensive analysis of the art of architecture and its impact on contemporary culture, transcending the boundaries of time and nationality. Previous studies on Prince Naris have often focused on the physical aspects of his ‘memory’ signs. However, our understanding of these signs is far more nuanced. To address this, a thorough review of literature on the subject of memory, as well as on Prince Naris himself, is necessary. This article draws extensively from primary sources, meticulously preserved by government sectors and private collections. Additionally, interviews with contemporary architects and artists from the Fine Arts Department, Thailand, provide valuable insights into the continued influence of Prince Naris’ designs. Three of Prince Naris’ works are analyzed, which clearly demonstrate his thinking about signs: first, the H.R.H. Prince Itsariyaphon monument; second, the Queen Mother Si Phatcharinthra crematorium and the talipot fans designed for her funeral ceremony; third, the design of a mythical creature, called “singha face,” at Benchama Bopitr Temple, which marks the position of H.M. King Chulalongkorn’s ashes. Prince Naris’ designs point to Thai beliefs in art and society. They are influenced by the treatise of Daksha (a form of astrology), which was popularly revised and published during the reigns of King Mongkut and King Chulalongkorn. This treatise outlined a system of belief regarding the day of birth (Monday, Tuesday, etc.), describing one’s fortune in relation to a specific day. Prince Naris’ designs intensify collective memories of the dead in built forms. He personalized monuments of death. This element of Prince Naris’ designs was a novelty, yet after his life, the repetition of memories gradually became popular amongst contemporary artists and architects. His designs perhaps marked the introduction of Thai tradition into the practice of memorializing the dead.